Domain-specific language for the configuration of network devices - Garzón Triana, Daniel Felipe; Montenegro Marín, Carlos Enrique; Gaona García, Paulo Alonso (Ingeniería Solidaria, 2016)
Introduction: This research is part of the project “Algorithm model for the implementation of configurations on network devices”, ascribed to the Master’s Degree of Information and Communications Sciences of the District University Francisco Jose de Caldas during the years 2015 and 2016. The detected issue is the search of configurations in network devices, which has proven to be a complex and repetitive task due to the wide variety of existent configurations.Methodology: This article presents the development of two domain-specific languages (dsl) based on mde. One is graphic: cnpGraph, and the other is textual: cnpText, as a proposed solution to the problem. Each tool generates a document with network protocols configurations required for network devices, regardless of the devices being routers or switches.Results: The tests were conducted using different scenarios and configurations, and comparing the search times through the use of domain-specific languages and conventional searches. The results show that cnpGraph and cnpText reduce in over 80 % the time used in finding the required configurations.Discussion: The main characteristic of both cnpGraph and cnpText is the possibility of increasing the amount of protocols and private brands of routers and switches, as well as associating protocols with the purpose of adding new network devices from different manufacturers and to access the necessary configuration in order to stablish every type of network.
Keywords: network devices; engineering directed by models; domain-specific languages; network protocols; Sirius; xText